Endoscopic Management of Foreign Bodies in the Upper Gastrointestinal Tract of Adults. (15th July 2015) - Yao, Chih-Chien; Wu, I-Ting; Lu, Lung-Sheng; Lin, Sheng-Chieh; Liang, Chih-Ming; Kuo, Yuan-Hung; Yang, Shih-Cheng; Wu, Cheng-Kun; Wang, Hsing-Ming; Kuo, Chung-Huang; Chiou, Shue-Shian; Wu, Keng-Liang; et al.
Abstract : Background . Foreign object ingestion and food bolus impaction are a common clinical problem. We report our clinical experiences in endoscopic management for adults, foreign body ingestion, and food bolus impaction. Method . A retrospective chart review study was conducted on adult patients with foreign body ingestion and food bolus impaction between January 2011 and November 2014. Patients with incomplete medical records were excluded. Results . A total of 198 patients (226 incidents) were included in the study (male/female: 1.54/1; age 57 ± 16 years). Among them, 168 foreign bodies were found successfully (74.3%). 75.6% of the foreign bodies were located in the esophagus. Food bolus impaction was most common (41.6%). 93.5% of foreign bodies in current study cohort were successfully extracted and 5 patients required surgical interventions. Comparisons between symptomatic and asymptomatic patients revealed that locations of foreign bodies in the pharynx and esophagus were the significant relevant factors (P < 0.001 ). Shorter time taken to initiate endoscopic interventions increased detection rate (289.75 ± 465.94 versus 471.06 ± 659.93 minutes, P = 0.028 ). Conclusion . Endoscopic management is a safe and highly effective procedure in extracting foreign body ingestion and food bolus impaction. Prompt endoscopic interventions can increase the chance of successful foreign bodies' detection.